Allicin enhances host pro-inflammatory immune responses and protects against acute murine malaria infection - Feng, Yonghui (BioMed Central, 2012)
BACKGROUND: During malaria infection, multiple pro-inflammatory mediators including IFN-γ, TNF and nitric oxide (NO) play a crucial role in the protection against the parasites. Modulation of host immunity is an important strategy to improve the outcome of malaria infection. Allicin is the major biologically active component of garlic and shows anti-microbial activity. Allicin is also active against protozoan parasites including Plasmodium, which is thought to be mediated by inhibiting cysteine proteases. In this study, the immunomodulatory activities of allicin were assessed during acute malaria infection using a rodent malaria model Plasmodium yoelii 17XL. METHODS: To determine whether allicin modulates host immune responses against malaria infection, mice were treated with allicin after infection with P. yoelii 17XL. Mortality was checked daily and parasitaemia was determined every other day. Pro-inflammatory mediators and IL-4 were quantified by ELISA, while NO level was determined by the Griess method. The populations of dendritic cells (DCs), macrophages, CD4(+) T and regulatory T cells (Treg) were assessed by FACS. RESULTS: Allicin reduced parasitaemia and prolonged survival of the host in a dose-dependent manner. This effect is at least partially due to improved host immune responses. Results showed that allicin treatment enhanced the production of pro-inflammatory mediators such as IFN-γ, TNF, IL-12p70 and NO. The absolute numbers of CD4(+) T cells, DCs and macrophages were significantly higher in allicin-treated mice. In addition, allicin promoted the maturation of CD11c(+) DCs, whereas it did not cause major changes in IL-4 and the level of anti-inflammatory cytokine IL-10. CONCLUSIONS: Allicin could partially protect host against P. yoelii 17XL through enhancement of the host innate and adaptive immune responses.